Streptomyces Volatile Compounds Influence Exploration and Microbial Community Dynamics by Altering Iron Availability - Stephanie E. Jones (American Society for Microbiology, 2019)
ABSTRACT Bacteria and fungi produce a wide array of volatile organic compounds (VOCs), and these can act as chemical cues or as competitive tools. Recent work has shown that the VOC trimethylamine (TMA) can promote a new form of Streptomyces growth, termed “exploration.” Here, we report that TMA also serves to alter nutrient availability in the area surrounding exploring cultures: TMA dramatically increases the environmental pH and, in doing so, reduces iron availability. This, in turn, compromises the growth of other soil bacteria and fungi. In response to this low-iron environment, Streptomyces venezuelae secretes a suite of differentially modified siderophores and upregulates genes associated with siderophore uptake. Further reducing iron levels by limiting siderophore uptake or growing cultures in the presence of iron chelators enhanced exploration. Exploration was also increased when S. venezuelae was grown in association with the related low-iron- and TMA-tolerant Amycolatopsis bacteria, due to competition for available iron. We are only beginning to appreciate the role of VOCs in natural communities. This work reveals a new role for VOCs in modulating iron levels in the environment and implies a critical role for VOCs in modulating the behavior of microbes and the makeup of their communities. It further adds a new dimension to our understanding of the interspecies interactions that influence Streptomyces exploration and highlights the importance of iron in exploration modulation. IMPORTANCE Microbial growth and community interactions are influenced by a multitude of factors. A new mode of Streptomyces growth—exploration—is promoted by interactions with the yeast Saccharomyces cerevisiae and requires the emission of trimethylamine (TMA), a pH-raising volatile compound. We show here that TMA emission also profoundly alters the environment around exploring cultures. It specifically reduces iron availability, and this in turn adversely affects the viability of surrounding microbes. Paradoxically, Streptomyces bacteria thrive in these iron-depleted niches, both rewiring their gene expression and metabolism to facilitate iron uptake and increasing their exploration rate. Growth in close proximity to other microbes adept at iron uptake also enhances exploration. Collectively, the data from this work reveal a new role for bacterial volatile compounds in modulating nutrient availability and microbial community behavior. The results further expand the repertoire of interspecies interactions and nutrient cues that impact Streptomyces exploration and provide new mechanistic insight into this unique mode of bacterial growth.